Stem cells and differentiation in vascular tissues - Hunziker, Pascal; Greb, Thomas (Annual review of plant biology, 2024)
Plant vascular tissues are crucial for the long-distance transport of water, nutrients, and a multitude of signal molecules throughout the plant body and, therefore, central to plant growth and development. The intricate development of vascular tissues is orchestrated by unique populations of dedicated stem cells integrating endogenous as well as environmental cues. This review summarizes our current understanding of vascular-related stem cell biology and of vascular tissue differentiation. We present an overview of the molecular and cellular mechanisms governing the maintenance and fate determination of vascular stem cells and highlight the interplay between intrinsic and external cues. In this context, we emphasize the role of transcription factors, hormonal signaling, and epigenetic modifications. We also discuss emerging technologies and the large repertoire of cell types associated with vascular tissues, which have the potential to provide unprecedented insights into cellular specialization and anatomical adaptations to distinct ecological niches.
Gesehen am 17.02.2025
Erstveröffentlichung als Rezension im Voraus am Februar 21, 2024